Effect of organic and inorganic sources of nutrients on soil fertility status of arecanut (Areca catechu) in north-east India - ACHARYA, G C; PAUL, S C; CHAKRABARTY, R; RAY, A K (The Indian Journal of Agricultural Sciences, 2015)
A study was conducted to assess the effect of three different sources of nutrients on soil fertility status in an adult arecanut (Areca catechu L.) plantation at Central Plantation Crops Research Institute, Research Centre, Guwahati, during 2008-09 and 2010-2011 in comparison with the planting time. The results revealed that the available nitrogen content was highest (332.6 and 242.3 kg/ha at 0-30 and 30-60 cm soil depth, respectively) in the soil applied with vermicompost, whereas the soils applied with chemical fertilizer recorded maximum available P and K content. However, the availability of these three major nutrients decreased with soil depth, irrespective of the sources of nutrient. Similar was in the case of organic carbon (OC) content and the soils applied with organics recorded higher value. Water holding capacity of soils was highest in organic plot over control and inorganic. Water holding capacity was significantly and positively correlated with organic carbon content but negatively correlated with bulk density of soil. Organic plots resulted almost 2.5 to 2.9 and 1.6 to 1.8 times higher earthworm population than fertilized plot and control plot respectively. Long-term application of compost improved soil physicochemical properties, available N content and also microbial population except available P and K content in soil which collectively resulted increased kernel yield of arecanut. Highest dry chali yield (4 496.9 kg/ha) of arecanut was obtained under vermicompost applied palms and was significantly higher than the chali yield of arecanut obtained under common compost and chemical fertilizer applied palms were 4 299.5 kg/ha, and 4 270.7 kg/ha, respectively.